El álbum coleccionable para la enseñanza de la unidad 3: Conquista y colonización de América, en el 9no EGB. - León Guamán, Josué Sebastián (2025)
The objective of this research work is to design a collectible album as a didactic resource to strengthen the teaching-learning process of Unit 3: Conquest and colonization of America of the Social Studies textbook for 9th grade EGB. Its approach is fundamentally mixed, which allowed the collection and analysis of qualitative information, as well as the analysis of quantitative data obtained after applying surveys to 104 students of 9th EGB of the Educational Unit “Juan de Velasco” and an interview to Social Studies teachers. Its design is descriptive, biographical/documentary and field, which allowed supporting this research whose variables have not been altered or manipulated. The results of this research reflect the clear need to implement novel didactic resources that attract the attention of students in order to improve their learning, since they have difficulties in learning and this is reflected in their level of knowledge. It also highlights that the proposed collectible album has a high level of approval by students and teachers, as it showed that students were attracted by it, their curiosity grew as well as their interest in the topics and contents of the resource, in addition to enhancing their social and collaborative skills, analysis and reflection, proving to be a good option to take into account in the classroom for the improvement of the teaching-learning process of student